International management : culture, strategy, and behavior - Luthans, Fred; Doh, Jonathan P. (New York, NY : McGraw Hill, 2021)
"The global business environment in recent years has been characterized by substantial and often unforeseen change. By some accounts, the degree of uncertainty and volatility in global political and economic affairs has increased as several long-term trends have come to a halt or, in some cases, reversed. Political conflicts, economic disruptions, and realignment of security arrangements have all created challenges for global business. Around the world, support for global economic integration and engagement appears to be on the decline. In this new, eleventh edition of International Management, we have retained the strong and effective foundations gained from research and practice over the past decades while incorporating the important latest research and contemporary insights that have changed the context and environment for international management. Several trends have emerged that pose both challenges and opportunities for international managers"--
Includes bibliographical references and index.
Keywords: International business enterprises -- Management; International business enterprises -- Management -- Case studies